(untitled) (Global Journal of Management and Business Research, 2019)
The study aimed to analyze published articles that deal with the fourth industrial revolution, the possibility and advantages of the merging of the sales and marketing divisions, the need for upskilling and reskilling of personnel in these functional divisions, with specific emphasis on their implications to speedy response to customer requirements. A thorough Systematic literature review and the synthesis of the major themes identified resulted in a proposed research framework for use by academics and management practitioners. The review concludes that there is a need to merge the Sales and Marketing divisions, to upskill and/or reskill personnel from these divisions in order to maintain or to gain a competitive urge. The resultant conceptual framework will serve as a springboard for the reconfiguration of the Sales and marketing divisions and the proper positioning organizations to survive and to succeed in the fourth industrial revolution environment.